A copolymer containing imidazole and piperidine structure and its preparation method and application
By using copolymers containing imidazole and piperidine structures in alkaline fuel cells, the problem of difficulty in achieving high ionic conductivity, alkali resistance and mechanical properties in the prior art is solved, and more efficient membrane material performance is achieved.
Patent Information
- Application Number
- CN202411696936.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The prior art is difficult to achieve high ionic conductivity, excellent alkali resistance and good mechanical properties in alkaline fuel cells at the same time.
By using copolymers containing imidazole and piperidine structures, the alkali resistance and mechanical properties of the membrane materials are enhanced by designing polymer functional group structures, using the resonance structure of imidazoles and the steric hindrance of piperidinium cations.
It achieves high ion conductivity, stable physical and chemical properties and excellent alkali resistance, balances the relationship between ion exchange capacity and mechanical strength, and significantly improves the performance of the anion membrane of alkaline fuel cell.
Smart Images

Figure CN119192545B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copolymer containing imidazole and piperidine structures and a preparation method and application thereof, belonging to the technical field of membrane materials. Background Art
[0002] In the current situation of rapid population growth, people's demand for clean energy has become more urgent due to the consumption of fossil fuels and natural gas and the increasing damage to the environment caused by these fuel resources. Nowadays, various environmental problems have attracted widespread attention, and the culprit of these environmental problems is the combustion of traditional fossil fuels, the main energy source for human activities, especially the global warming caused by large amounts of carbon dioxide emissions and air pollution caused by SOx and NOx emissions. In addition, the reserves of fossil fuels are limited, while the world's population and energy demand are continuing to grow. In the face of these problems, the development of new clean energy such as solar energy, wind energy, geothermal energy and other renewable energy sources has received more and more attention, and its capacity and proportion in the world's energy supply have continued to rise. However, the intermittent nature of renewable energy limits their application prospects. In order to strengthen the research and development of new technologies, a more efficient energy conversion system is needed to balance the intermittent energy production. In this context, fuel cell technology has shown great advantages.
[0003] Compared with other types of fuel cells, alkaline anion exchange membrane fuel cells have more advantages, such as: higher reaction efficiency; allowing the use of non-precious metals such as silver and nickel as catalysts; better tolerance to carbon monoxide in gas raw materials, etc. Based on these advantages, alkaline anion fuel cells have been considered as the next generation of new and efficient fuel cell technology in recent years, and people have invested a lot of research and development applications in this regard.
[0004] How to make anion exchange membranes have both high ion conductivity and excellent alkali resistance is an important challenge in preparing effective anion exchange membranes. When designing polymer structures, the ion exchange capacity (IEC) can be increased by increasing the charged functional groups in the molecular structure, further improving the ion conductivity; however, high ion exchange capacity (IEC) means high water absorption, which will affect the stability of mechanical properties. Therefore, it is also possible to make a comprehensive consideration from the rigidity of the polymer skeleton and the type of polymer main chain. In general, mechanical properties and electrochemical properties exist in opposition. In order to obtain a suitable anion exchange membrane for alkaline fuel cells, it is necessary to use various properties to balance ion exchange capacity and mechanical strength. The second is the alkali resistance of the anion exchange membrane to prevent the membrane material from being degraded by the attack of hydroxide in an alkaline environment, which greatly reduces the efficiency of the fuel cell. The functional group structure of the polymer can be designed, such as using the resonance structure in the functional groups such as imidazoles and quaternary phosphine groups to achieve the weakening of hydroxide attack, delay the degradation of the anion membrane, and improve the service life of the membrane material. In general, the main requirements for ion exchange membranes for alkaline fuel cells are: low cost, good mechanical properties, the ability to conduct hydroxide ions with high ionic conductivity, and excellent alkali resistance. Summary of the invention
[0005] The present invention aims at the deficiencies in the prior art and provides a copolymer containing imidazole and piperidine structures and a preparation method and application thereof. The ion exchange membrane material prepared by using the copolymer has good ion conductivity, stable physical and chemical properties and excellent alkali resistance. The preparation method is simple and easy, and the copolymer has great potential in the application of anion membranes in alkaline fuel cells.
[0006] The technical solution of the present invention to solve the above technical problem is as follows: a copolymer containing imidazole and piperidine structure, wherein the copolymer containing imidazole and piperidine structure comprises the following structure:
[0007] ;
[0008] Y1 and Y2 are each independently selected from aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl or absent, and at least one of Y1 and Y2 is selected from aryl, aralkyl, heteroalkyl, alkyl or perfluoroalkyl. When one of Y1 and Y2 is absent, the group to which the existing Y1 or Y2 is connected is neutral;
[0009] Y3 and Y4 are each independently selected from aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl or absent, and at least one of Y3 and Y4 is selected from aryl, aralkyl, heteroalkyl, alkyl or perfluoroalkyl, and when one of Y3 and Y4 is absent, the imidazole group to which the existing Y3 or Y4 is connected is neutral;
[0010] Y5 and Y6 are each independently selected from aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl or absent, and at least one of Y5 and Y6 is selected from aryl, aralkyl, heteroalkyl, alkyl or perfluoroalkyl, and when one of Y5 and Y6 is absent, the imidazole group to which the existing Y5 or Y6 is connected is neutral;
[0011] Ar1, Ar2, Ar3, Ar5, Ar6 are each independently selected from substituted or unsubstituted arylene, aralkylene, heteroalkylene, alkylene, perfluoroalkylene, heteroarylene or absent; when Ar1, Ar2, Ar3, Ar5, Ar6 contain substituents, they are substituted by 1, 2, 3 or 4 substituents, and the substituents are independently selected from alkyl, aryl, aralkyl, perfluoroalkyl, heteroalkyl, heteroaryl and halogen;
[0012] Ar4, Ar7 are each independently selected from substituted or unsubstituted aryl, aralkyl, heteroalkyl, alkyl, perfluoroalkyl, heteroaryl or hydrogen; when Ar4 or Ar7 contains substituents, they are substituted by 1, 2, 3, 4 or 5 substituents independently selected from alkyl, aryl, aralkyl, perfluoroalkyl, heteroalkyl, heteroaryl and halogen;
[0013] R1, R2, R3, R4, R5, R6, R7, R8 are each independently selected from hydrogen, alkyl, aryl, aralkyl, heteroalkyl, heteroaryl and perfluoroalkyl;
[0014] The heteroatoms in the above heteroalkyl, heteroaryl, heteroalkylene and heteroarylene groups are selected from O, N and S;
[0015] M - Any one or any combination thereof selected from fluoride, chloride, bromide, iodide, hydroxide, carbonate, bicarbonate, cyanide, sulfate, phosphate, and trifluoromethanesulfonate;
[0016] x and y are the percentages of the two structures in the box, x is an arbitrary value between 0.01 and 0.99, y is an arbitrary value between 0.01 and 0.99, and x+y=1;
[0017] n is an integer between 10 and 1,000,000.
[0018] Furthermore, the copolymer comprises one or more anions M - , where one or more anions M - Counteract one or more positive charges in the copolymer.
[0019] Furthermore, the copolymer containing imidazole and piperidine structures includes the following structure:
[0020] .
[0021] Furthermore, Ar1, Ar2, Ar3, Ar5, and Ar6 are each independently selected from an arylene group or do not exist; Ar4 and Ar7 are each independently selected from an aryl group; Y1, Y2, Y3, Y4, Y5, and Y6 are each independently selected from a C1-C5 alkyl group; R3, R4, R7, and R8 are each independently selected from hydrogen and a C1-C5 alkyl group.
[0022] Further, the copolymer is selected from any one of the following structures:
[0023] .
[0024] The present invention also discloses a method for preparing a copolymer containing imidazole and piperidine structures, the preparation method comprising the following steps:
[0025] S1. Polymerization reaction:
[0026] Under the protection of inert gas, the monomer is dissolved in a solvent, a catalyst and a ligand are added, and then the polymerization is carried out by heat preservation until the reaction system reaches a desired viscosity, and then the polymerization is stopped. After post-treatment, a copolymer containing imidazole and piperidine structures is obtained;
[0027] Wherein, the monomer combination is: and , X is iodine, bromine or chlorine;
[0028] S2. Functionalization:
[0029] The copolymer containing imidazole and piperidine structure obtained in step S1 is dissolved in a solvent, and then a functionalizing agent is added. After the reaction is completed with sealed, heat-insulated and stirred reaction under heating conditions, a functionalized copolymer containing imidazole and piperidine structure is obtained through post-treatment.
[0030] Further, the monomer combination is selected from any group of the following structures:
[0031] ; ;
[0032] ; .
[0033] Further, the solvent is any one or a combination of dimethyl sulfoxide, N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide;
[0034] The catalyst is any one of trans-1,5,9-cyclododecatriene nickel (0), nickel chloride, and nickel chloride ethylene glycol dimethyl ether complex, and the ligand is 2,2'-bipyridine;
[0035] The functionalizing agent is any one of iodomethane, iodoethane, iodopropane, iodobutane, iodopentane, iodohexane, iodoheptane, iodooctane, iodononane and iododecane;
[0036] The post-processing process of step S1 and step S2 is: pouring the reaction solution into a precipitant, filtering, washing, and drying to obtain the target product;
[0037] The precipitant is any one or a combination of purified water, industrial hydrochloric acid, phosphoric acid, dilute sulfuric acid, hydrobromic acid, hydrofluoric acid, hydroiodic acid, cyanic acid, and trifluoromethanesulfonic acid.
[0038] Furthermore, in step S1, the dissolution temperature of the monomer in the solvent is 20.0°C-60.0°C, the reaction temperature of the heat preservation polymerization is 130.0°C-135.0°C, and the heat preservation polymerization reaction time is 10h-30h;
[0039] In step S2, the heating temperature is 30°C-50°C, and the stirring time is 12h-36h;
[0040] During the post-treatment process, the filtering and washing temperatures are 20.0°C-30.0°C; the drying temperature is 90.0°C-120.0°C, and the drying time is more than 24 hours.
[0041] The invention also discloses the application of a copolymer containing imidazole and piperidine structures, wherein the copolymer is applied to an ion exchange membrane for a fuel cell or for producing hydrogen by hydrolyzing water.
[0042] The preparation method of the ion exchange membrane of the fuel cell is as follows: the dried copolymer material is dissolved in isopropanol to obtain a uniform solution with a mass fraction of 10%, the film is coated on a clean glass plate, and the ion exchange membrane is carefully peeled off after drying, and the ion exchange membrane is immersed in a 1M potassium hydroxide solution, activated for 24h-48h, and then washed with purified water until the aqueous solution is neutral, and dried to obtain the ion exchange membrane material prepared by the copolymer of the present invention.
[0043] The beneficial effects of the present invention are:
[0044] The copolymer containing imidazole and piperidine structure of the present invention makes full use of the structural characteristics of polymer functional groups, such as: utilizing the resonance structure in the functional group of imidazole, and the intra-ring conjugated large π bond and large steric hindrance in the imidazolium salt, so that the positive charge is delocalized and evenly dispersed in the imidazole ring, weakening the aggressiveness of the hydroxide ion; utilizing the highly alkaline and stable piperidinium cation to enhance the alkali resistance of the membrane material. At the same time, the main chain structure of the polymer contains aromatic rings such as biphenyl and naphthalene, which enhances the rigidity of the membrane material. Therefore, this membrane material not only has high alkali resistance, but also can effectively control the water absorption and swelling rate of the membrane material, and very well balances the relationship between ion exchange capacity (IEC) and mechanical strength.
[0045] In summary, the ion exchange membrane material prepared using the copolymer of the present invention has high alkali resistance and good mechanical properties, as well as good ion conductivity and appropriate swelling degree, so it has great potential for application in anion membranes of alkaline fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The comparison diagram of the relationship between the swelling degree and temperature of the A film, the B film, the C film, the D film, and the E film;
[0047] Figure 2 This is a comparison chart of the stability of membrane A, membrane B, membrane C, membrane D, and membrane E when immersed in 2M sodium hydroxide solution at 80.0°C;
[0048] Figure 3 This is a comparison chart of the relationship between the ion conductivity and temperature of membrane A, membrane B, membrane C, membrane D, and membrane E;
[0049] Figure 4 This is the discharge polarization curve of the hydrogen-oxygen anion exchange membrane single cell prepared using membrane B. DETAILED DESCRIPTION
[0050] The specific implementation of the present invention is described in detail below. In the polymer structure of the embodiment, x and y are the percentages of the two structures in the frame, both of which are 50%. The listed polymer structure only shows one possible molecular structure, and does not mean that all molecular chains have this structure, because it is a copolymer, and the connection mode inside the molecular chain is diverse.
[0051] The coatings and various testing methods mentioned in the specific embodiments are commonly used methods in the industry and are intended to compare the performance of the film materials mentioned in the embodiments.
[0052] The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0053] 1. Polymer Preparation Example
[0054] Example 1
[0055] An anion exchange membrane material used in fuel cells, the structural formula of polymer A is:
[0056] ;
[0057] The specific synthetic route of polymer A is:
[0058] ;
[0059] Preparation of A-1: 1,4-benzenedicarboxaldehyde (CAS: 623-27-8), 1-(4-chlorophenyl)-2-phenylethane-1,2-dione (CAS: 22711-23-5) and ammonium acetate (CAS: 631-61-8) were weighed in a molar ratio of 1:2.2:12, the solvent was glacial acetic acid, and the amount of the solvent was 10.0 times the weight of 1-(4-chlorophenyl)-2-phenylethane-1,2-dione (CAS: 22711-23-5), and then kept at 110°C for 4 hours. HPLC detection showed that there was no residue of raw materials and the reaction purity was 88.5%. A-1 was obtained after hydrolysis, filtration, boiling and beating, with a yield of 80.5% and an HPLC purity of 97.2%. 1 H NMR (500 MHz, Chloroform- d ): 12.09 (s, 1H), 12.03 (s,1H), 7.88 (s, 4H), 7.56-7.51 (m, 2H), 7.51-7.47 (m, 2H), 7.47-7.37 (m, 9H),7.36 (d, 1H), 7.34-7.24 (m, 4H). LC-MS detection: theoretical molecular weight is 583.53, and the actual detection result molecular weight is 583.0.
[0060] Preparation of A-2: A-1 and potassium hydroxide were weighed at a molar ratio of 1.0:2.2, the solvent was dimethyl sulfoxide, and the amount of solvent was 10.0 times the weight of A-1, and then methyl iodide and A-1 were weighed at a molar ratio of 2.2:1, methyl iodide was added dropwise at 30°C, and then the reaction was kept warm for 2 hours. HPLC detection showed that the reaction purity was 96.5%. A-2 was obtained after hydrolysis, filtration, boiling, and beating, with a yield of 88.1% and an HPLC purity of 99.5%. 1 H NMR (500 MHz, Chloroform- d ): 7.79 (s, 4H), 7.63-7.57 (m,2H), 7.55-7.50 (m, 2H), 7.50-7.32 (m, 13H), 7.32 (d, 1H), 3.83 (s, 6H). LC-MS: The theoretical molecular weight is 611.56, and the actual molecular weight is 611.0.
[0061] Preparation of A-3: 1-methyl-4-piperidone (CAS: 1445-73-4) and trifluoromethanesulfonic acid (CAS: 1493-13-6) were weighed at a molar ratio of 1.0:3.0, the substrate solvent was chlorobenzene, the amount of solvent was 5.0 times the weight of 1-methyl-4-piperidone (CAS: 1445-73-4), the temperature was controlled at about 0°C and trifluoromethanesulfonic acid was added dropwise, after the addition was completed, the temperature was raised to 20-30°C and kept for 2 hours, and the reaction purity was 85.5% after GC detection. A-3 was obtained through hydrolysis, alkalization, extraction, water washing, solvent removal, and recrystallization, with a yield of 73.1% and a GC purity of 97.5%. 1 H NMR (500 MHz, Chloroform- d ): 7.32-7.26 (m, 4H), 7.19-7.13 (m, 4H), 2.67 (t, 4H), 2.33-2.26 (m, 7H). GC-MS: The theoretical molecular weight is 320.26, and the actual molecular weight is 320.1.
[0062] Preparation of A-4: A-2 and A-3 were weighed at a molar ratio of 1.0:1.0, and then A-2 and N,N-dimethylformamide were weighed at a weight ratio of 1.0:30.0. A-2 and A-3 were dissolved in N,N-dimethylformamide, and nickel chloride and 2,2'bipyridine were added at low temperature and under the protection of inert gas. The molar ratio of A-2 to catalyst and ligand was 1.0:4.0:4.0. Then the reaction was kept at 130°C for 20 hours. When the system was a viscous liquid, the heat preservation reaction was stopped. The reaction solution was controlled to be below 30.0°C, slowly hydrolyzed into hydrochloric acid for precipitation, and then filtered, washed, and dried to obtain A-4.
[0063] Preparation of polymer A: A-4 was dissolved in 40.0 times of N,N-dimethylformamide, A-4 and 1-iodobutane were weighed in a molar ratio of 1.0:6.0, and the mixture was stirred in a closed manner at 30°C for 30 hours. The reaction solution was hydrolyzed into hydrochloric acid for precipitation, and polymer A was obtained after filtration, washing and drying.
[0064] Example 2
[0065] An anion exchange membrane material used in fuel cells, the structural formula of polymer B is:
[0066] ;
[0067] The specific synthetic route of polymer B is:
[0068] ;
[0069] The preparation of polymer B is different from that of polymer A in that the raw material 1-methyl-4-piperidone (CAS: 1445-73-4) in the preparation of A-3 is replaced with 1,2,2,6,6-pentamethyl-4-oxopiperidine (CAS: 5554-54-1), and then polymer B is prepared according to the process for preparing polymer A.
[0070] Example 3
[0071] An anion exchange membrane material used in a fuel cell, the structural formula of the polymer C is:
[0072] ;
[0073] The specific synthetic route of polymer C is:
[0074] ;
[0075] The difference between the preparation of polymer C and the preparation of polymer B is that the raw material 1,4-benzenedicarbaldehyde (CAS: 623-27-8) in the preparation of A-1 is replaced with 1,5-naphthalenedicarbaldehyde (CAS: 7141-15-3), and then polymer C can be prepared according to the process for preparing polymer B.
[0076] Embodiment 4:
[0077] An anion exchange membrane material used in fuel cells, the structural formula of polymer D is:
[0078] ;
[0079] The specific synthetic route of polymer D is:
[0080] ;
[0081] The preparation of polymer D is different from that of polymer A in that: D-1 can be prepared by replacing the raw material 1,4-benzenedicarboxaldehyde (CAS: 623-27-8) in the preparation of A-1 with [1,1'-biphenyl]-4,4'-dicarboxaldehyde (CAS: 66-98-8); D-3 can be prepared by replacing the raw material chlorobenzene in the preparation of A-3 with 4-chlorobiphenyl (CAS: 2051-62-9), and then polymer D can be prepared according to the process for preparing polymer A.
[0082] Comparative Example 1
[0083] Fuel cell anion exchange membrane polymer E structure:
[0084] ;
[0085] According to the information disclosed in Chinese patent CN116693785B, the F2h diaphragm material in Example 2 mentioned in the patent was prepared.
[0086] 2. Polymer Application: Coating and Related Testing
[0087] Coating: The polymers A, B, C, D and E synthesized in the above Examples 1, 2, 3, 4 and Comparative Examples are respectively prepared into casting liquids with a mass fraction of 10% with isopropanol. Then, the casting liquids are respectively coated on clean glass plates with a scraper, and the coating thickness is 40-50 microns. Then, the solvent is evaporated and carefully peeled off to obtain the corresponding ion exchange membrane material. Then, the ion exchange membrane is functionalized and respectively invaded into a 1M potassium hydroxide solution. After soaking for 48 hours, the membrane is taken out and washed with deionized water until the aqueous solution is neutral. Then, it is dried at 100°C for 48 hours to obtain the corresponding hydroxide-type alkaline fuel cell anion exchange membranes of polymers A, B, C, D and E: A membrane, B membrane, C membrane, D membrane and E membrane. Then, the A membrane, B membrane, C membrane, D membrane and E membrane are subjected to relevant tests and the single cell performance test of the corresponding membranes:
[0088] (1) Solubility test: 1.0 g of polymer was added to 30.0 g of solvent, heated at 80.0 °C and stirred to aid dissolution, and the dissolution was observed.
[0089] Intrinsic viscosity test: The polymers were dissolved in dimethyl sulfoxide to prepare a clear solution with a concentration of 1.0%, and measured with an Ubbelohde viscometer at 23.0°C. The specific test results are shown in Table 1 below.
[0090] Table 1 Viscosity and solubility of membrane materials
[0091]
[0092] Note: ++ means soluble at room temperature, +- means swellable at room temperature, and -- means insoluble even when heated.
[0093] Table 1 shows the viscosity and solubility of film A, film B, film C, film D, and film E. Based on the solubility of each film and the ease of solvent removal, isopropyl alcohol was selected as the film coating solvent. The viscosity of each film is moderate, meeting the needs of film coating.
[0094] (2) Water absorption and swelling ratio: Use a knife to cut several 10mm*50mm small sample strips, vacuum dry them at 80℃ for 24h, quickly measure their dry weight, and then soak them in a constant temperature water bath at 40℃ and 80℃ for 24h, wipe the surface of the membrane with filter paper, and weigh its water absorption weight. Then place the membrane on a glass plate, measure the length of the membrane with a vernier caliper, and calculate the water absorption (water up) and volume swelling ratio (swelling ratio) of the membrane. The calculation formulas for water absorption and swelling ratio are as follows: Water absorption = m a -m b / m a ×100%, swelling rate = l a -l b / l b ×100%, where m a , l a m are the mass and length of the membrane after immersion in a water bath at a specific temperature for 24 hours; m b , l b The specific test results are shown in Table 2 below.
[0095] Table 2 Water absorption of membrane materials
[0096]
[0097] Figure 1 Table 2 is the corresponding relationship between the swelling degree and temperature of membrane A, membrane B, membrane C, membrane D, and membrane E. Table 3 is the water absorption rate of membrane materials. Alkaline anion exchange membrane can conduct hydroxide ions better only after absorbing a certain amount of water. At this time, the size of the membrane will change moderately and swelling will occur. However, excessive swelling degree and water absorption rate will cause excessive changes in the mechanical properties and morphology of the membrane, which may cause problems such as catalyst shedding. Based on parameters such as water absorption rate and swelling degree, membrane A, membrane B, membrane C, membrane D, and membrane E can meet the basic use requirements of alkaline fuel cell membranes.
[0098] (3) Alkali stability: The membrane material was immersed in a 2 M potassium hydroxide solution at 80.0°C. A sample was taken out every 120 h. The membrane material was washed with deionized water until the aqueous solution was neutral. The ionic conductivity of the membrane material was then tested. The alkaline stability of the membrane was determined by the retention rate of the ionic conductivity.
[0099] Figure 2The stability of the membrane material immersed in 2M potassium hydroxide solution at 80.0℃. From the data, it can be analyzed that the conductivity of membrane A, membrane B, membrane C, and membrane D is kept in alkaline solution for 960 hours, and the conductivity of membrane E is kept in alkaline solution for 960 hours, and the conductivity is kept above 80%. The difference in alkali resistance may be due to the difference in the stability of the polymer main chain structure. When applied, the working environment of the membrane is strongly alkaline. Alkali stability is crucial for membrane materials and is an important consideration factor related to the life of alkaline fuel cells. Although the alkali resistance of membrane E is better, the alkali resistance of membrane A, membrane B, membrane C, and membrane D is more superior, and the degradation rate of membrane E is significantly accelerated after 720 hours, while there is no obvious change in the other membranes. The better alkali resistance of the membrane material can keep it stable in a strongly alkaline working environment and ensure the service life of the membrane material.
[0100] (4) Ionic conductivity: The ionic conductivity was tested by the AC impedance method. The in-plane conductivity of the ion membrane was measured using an electrochemical workstation (CHI660C, Shanghai Chenhua Instrument Co., Ltd., Shanghai). The test frequency was 1 to 10 5 Hz. During the test, the ion membrane is clamped in a tetrafluoroethylene mold with two platinum electrodes, and the AC impedance test is performed in constant current mode. Ionic conductivity = distance between two electrodes / cross-sectional area of the membrane in the electric field / membrane resistance.
[0101] Figure 3 The relationship between the ion conductivity of the membrane material and the temperature. As the temperature rises, the water absorption rate of the membrane increases, the membrane material partially swells, and the diffusion rate of water accelerates, and the ion conductivity of the membrane material increases. From the comprehensive data, the conductivity of membrane A, membrane B, membrane C, membrane D, and membrane E can meet the basic use requirements of alkaline fuel cell membranes, but the conductivity of membrane A, membrane B, membrane C, and membrane D is more superior, making the performance of alkaline fuel cells better.
[0102] (5) In order to evaluate the practical application effect of the highly stable ion exchange membrane of the present invention, a membrane B with better comprehensive parameters was selected to assemble the membrane electrode first, and then made into a single cell for performance testing.
[0103] Preparation of membrane electrode: First, the membrane electrode assembly is prepared by CCS method, that is, the catalyst ink is sprayed on carbon paper, and then the carbon paper and membrane material are contacted by hot pressing. The cathode and anode catalysts are platinum carbon and platinum ruthenium carbon respectively, and the loading of metal platinum is 1mg / cm 2 The mass ratio of catalyst to ion polymer is 4.0:1.0, then the catalyst, isopropanol, and polymer dimethyl sulfoxide solution (5.0% mass fraction) are mixed and dispersed evenly by ultrasound. The mixed solution is evenly sprayed on carbon paper to make a gas diffusion electrode. The membrane is sandwiched between the two electrodes, and the electrodes and the membrane are pressed into a membrane electrode assembly by external force at room temperature.
[0104] Single cell assembly and performance test: The sealing gasket, graphite flow field, gold-plated current collector, insulating pad and heating end plate are assembled on both sides of the membrane electrode to obtain a single cell. The effective area of the electrode is 1cm 2 The performance was tested using a fuel cell workstation (Arbin Instrument, College station, TX) under the following conditions: at 60.0°C, a hydrogen flow rate of 500 mL / min, an oxygen flow rate of 150 mL / min, and a relative humidity of 100%.
[0105] Figure 4 This is the discharge polarization curve of a single hydrogen-oxygen anion exchange membrane cell. From the test data, we can see that the open circuit voltage of the single cell is 1.05V and the maximum power density of the single cell is 532mW / cm 2 When the maximum power density is reached, the corresponding current density is 750.0mA / cm 2 , the voltage is 0.71 V. The single cell maintains good operating stability within the observed time interval of the test, which fully demonstrates that the high-performance ion exchange membrane obtained by the present invention can be used as a membrane material for fuel cells.
[0106] It can be seen from the above relevant test data that the A membrane, B membrane, C membrane and D membrane can well meet the use requirements of the alkaline fuel cell ion exchange membrane. The membrane electrode assembly prepared with the B membrane has also been proved by the single cell performance test that this copolymer material can be used as a membrane electrode material for fuel cells. Compared with the publicly reported E membrane (prepared according to patent number: CN116693785B), the comprehensive performance of the A membrane, B membrane, C membrane and D membrane is more outstanding. The membrane material prepared by the copolymer of the present invention, when used for the membrane electrode in the alkaline fuel cell, not only has good ion conductivity and moderate swelling rate, but also has excellent alkali resistance. Therefore, the ion exchange membrane material prepared by the copolymer designed by the present invention has great potential in the application of anion membranes in alkaline fuel cells.
[0107] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0108] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A copolymer containing imidazole and piperidine structure, characterized in that: The copolymer containing imidazole and piperidine structure includes the following structure: ; Ar1, Ar2, Ar3, Ar5, Ar6 are each independently selected from arylene; Ar4, Ar7 are each independently selected from aryl; Y1, Y2, Y3, Y4, Y5, Y6 are each independently selected from C1-C5 alkyl; R3, R4, R7, R8 are each independently selected from hydrogen, C1-C5 alkyl; M - Any one or any combination thereof selected from fluoride, chloride, bromide, iodide, hydroxide, carbonate, bicarbonate, cyanide, sulfate, phosphate, and trifluoromethanesulfonate; x and y are the percentages of the two structures in the box, x is an arbitrary value between 0.01 and 0.99, y is an arbitrary value between 0.01 and 0.99, and x+y=1; n is an integer between 10 and 1,000,000.
2. A copolymer containing imidazole and piperidine structure according to claim 1, characterized in that: The copolymer comprises one or more anions M - , where one or more anions M - Counteract one or more positive charges in the copolymer.
3. The copolymer containing imidazole and piperidine structure according to claim 1, characterized in that: The copolymer is selected from any one of the following structures: 。 4. A method for preparing a copolymer containing imidazole and piperidine structures according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1. Polymerization reaction: Under the protection of inert gas, the monomer is dissolved in a solvent, a catalyst and a ligand are added, and then the polymerization is carried out by heat preservation until the reaction system reaches a desired viscosity, and then the polymerization is stopped. After post-treatment, a copolymer containing imidazole and piperidine structures is obtained; Wherein, the monomer combination is: and , X is iodine, bromine or chlorine; R1, R2, R5, R6 are each independently selected from hydrogen; S2. Functionalization: The copolymer containing imidazole and piperidine structure obtained in step S1 is dissolved in a solvent, and then a functionalizing agent is added. After the reaction is completed with sealed, heat-insulated and stirred reaction under heating conditions, a functionalized copolymer containing imidazole and piperidine structure is obtained through post-treatment.
5. The method for preparing a copolymer containing imidazole and piperidine structure according to claim 4, characterized in that: The monomer combination is selected from any group of the following structures: ; ; ; 。 6. The method for preparing a copolymer containing imidazole and piperidine structure according to claim 4, characterized in that: The solvent is any one or a combination of dimethyl sulfoxide, N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide; The catalyst is any one of trans-1,5,9-cyclododecatriene nickel (0), nickel chloride, and nickel chloride ethylene glycol dimethyl ether complex, and the ligand is 2,2'-bipyridine; The functionalizing agent is any one of iodomethane, iodoethane, iodopropane, iodobutane, iodopentane, iodohexane, iodoheptane, iodooctane, iodononane and iododecane; The post-processing process of step S1 and step S2 is: pouring the reaction solution into a precipitant, filtering, washing, and drying to obtain the target product; The precipitant is any one or a combination of purified water, industrial hydrochloric acid, phosphoric acid, dilute sulfuric acid, hydrobromic acid, hydrofluoric acid, hydroiodic acid, cyanic acid, and trifluoromethanesulfonic acid.
7. The method for preparing a copolymer containing imidazole and piperidine structure according to claim 6, characterized in that: In step S1, the dissolution temperature of the monomer in the solvent is 20.0°C-60.0°C, the reaction temperature of the heat preservation polymerization is 130.0°C-135.0°C, and the heat preservation polymerization reaction time is 10h-30h; In step S2, the heating temperature is 30°C-50°C, and the stirring time is 12h-36h; During the post-treatment process, the filtering and washing temperatures are 20.0°C-30.0°C; the drying temperature is 90.0°C-120.0°C, and the drying time is more than 24 hours.
8. An application of a copolymer containing imidazole and piperidine structure according to any one of claims 1 to 3, characterized in that: The copolymer is applied to an ion exchange membrane for a fuel cell or for producing hydrogen by hydrolyzing water.
Citation Information
Patent Citations
A type of nitrogen-containing heterocyclic polymer, a type of polymer film and its application
CN116693785B
High-strength alkaline anionic polymer cross-linked membrane and preparation method thereof
CN112759778A